Synthesis of CuxS Thin Films with Tunable Localized Surface Plasmon Resonances - Kalanur, Shankara S.; Seo, Hyungtak (ChemistrySelect, 2018)
In this work, we report the fabrication of copper sulfide (CuS, Cu1.39S, and Cu2S) thin films with tunable localized surface plasmon resonance (LSPR). The thin films were synthesized by keeping the Cu precursor concentration constant and varying that of sodium thiosulfate, which dictated the final CuxS product. CuS showed the highest intensity LSPR peak and its intensity decreased with the increasing incorporation of Cu, as in the case of Cu1.39S, and vanished for the Cu-rich Cu2S, indicating carrier concentration-dependent plasmonic absorption. The shift in the XRD peak positions towards a lower degree and the increase in the d-spacing values for CuS indicated the intercalation of Cu species in the initial covellite lattice, yielding Cu1.39S and Cu2S in the process. XPS valence band edge studies revealed that among the synthesized CuxS thin films, CuS showed a stronger p-type as compared to Cu1.39S and Cu2S.
Keywords: copper sulfide; localized surface plasmon resonances; p-type; tunable LSPR; valency